Lie to me: verbal and nonverbal cues indicating deception versus honesty among English speaking students in higher education institution - Zulkarnain, Nur Azwin; Mokhtar, Nor Zainiyah Norita (IIUM Press, International Islamic University Malaysia, 2017)
This book discussed the para-social interaction between young adults of IIUM and public figures of their choice. It considers the power distance as the determining factor that influence the para-social interaction between them. On another aspect, this study also looks at the attitudes that the young adults develop towards the public figures based on the influence of power of the public figures. To do so, an adaptation of Celebrity Worship Scale developed by McCutcheon et al (2002) with some alteration was used. Such modification was deemed necessary as the questionnaire is from Western country and making it localized helped to draw a more concrete conclusion. The results show that there is strong para-social interaction between young adults and public figures of their choice and the attitudes of the young adults towards public figures.